Neck circumference as a predictor of cardiovascular risk in chronic kidney disease patients on hemodialysis (Research, Society and Development, 2022)
The present study aimed to evaluate neck circumference as a predictive parameter of cardiovascular risk in renal patients undergoing hemodialysis. This is a cross-sectional study with 103 patients with chronic kidney disease undergoing hemodialysis, evaluated from July 2018 to September 2019, in two hemodialysis clinics located in the metropolitan region of Recife-PE. Cardiovascular risk was assessed from neck circumference using the Neck Circumference ≥ 37 cm for men and ≥ 34 cm for women cut-off points, as described by BenNoun, Sohar and Laor. Sociodemographic and lifestyle characteristics, as well as traditional anthropometric parameters and indices, were evaluated. In addition, biochemical parameters such as lipid profile, blood glucose, vitamin D, among others, were evaluated. To assess the association between the variables and cardiovascular risk, the chi-square with Yates correction and the McNemar test were used. To verify the correlations, Pearson's correlation was used. Variables with a value of p≤10 were considered borderline significance and those with p